ANALISIS KOMUNIKASI PEMASARAN BAJU BATIK TULIS DALAM FACEBOOK PAGE - Ignasius Wandelius Dua; Herman (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2014)
This research is motivated by the growing of facebook page in facebook site . Many owners offacebook page started to introduce new products with features of facebook page. Starting from the online store owned by individuals , large companies, small and medium enterprises (SME's), even an amateur businessman began developing his facebook page in facebook. The company delivered the message with varied forms of communication, with different purpose and intent of each message who sent by the company facebook page. The purpose of this research is to describe the marketing communication activities that occur between the companies and the consumers that happen in facehook page of 'Baju Batik Tulis'.This rsearch used a qualitative approach with descriptive methods. Collection of data is done by observation, interview and documentation techniques. Structured observations made in the wall of facebook page of 'baju batik t nils', starting from the 3 latest months when the research was conducted . Interviews were conducted to 20 respondents fans of 'baju batik tulis \ as an amplifier of observation data. Documentation technique is used to take the documents that stored in the Uniform Resource Locator ( URL ) of facebook page of 'Baju Batik Tulis \ This research found that marketing communications is applied by the owner in facebook page with varied strategies. Marketing